A 6-alkylsalicylate histone acetyltransferase inhibitor inhibits histone acetylation and pro-inflammatory gene expression in murine precision-cut lung slices. (June 2017) - van den Bosch, Thea; Leus, Niek G.J.; Wapenaar, Hannah; Boichenko, Alexander; Hermans, Jos; Bischoff, Rainer; Haisma, Hidde J.; Dekker, Frank J.
Abstract: Lysine acetylations are post-translational modifications of cellular proteins, that are crucial in the regulation of many cellular processes. Lysine acetylations on histone proteins are part of the epigenetic code regulating gene expression and are installed by histone acetyltransferases. Observations that inflammatory lung diseases, such as asthma and chronic obstructive pulmonary disease, are characterized by increased histone acetyltransferase activity indicate that development of small molecule inhibitors for these enzymes might be a valuable approach towards new therapies for these diseases. The 6-alkylsalicylate MG149 is a candidate to explore this hypothesis because it has been demonstrated to inhibit the MYST type histone acetyltransferases. In this study, we determined the Ki value for inhibition of the MYST type histone acetyltransferase KAT8 by MG149 to be 39 ± 7.7 μM. Upon investigating whether the inhibition of histone acetyltransferases by MG149 correlates with inhibition of histone acetylation in murine precision-cut lung slices, inhibition of acetylation was observed using an LC-MS/MS based assay on histone H4 res 4–17, which contains the target lysine of KAT8. Following up on this, upon treatment with MG149, reduced pro-inflammatory gene expression was observed in lipopolysaccharide and interferon gamma stimulated murine precision-cut lung slices. Based on this, we propose that 6-alkylsalicylates such as MG149 have potential for development towards applications in the treatment of inflammatory lung diseases. Graphical abstract: